Vibration of workpieces during aggressive turning operations - Han, X; Wang, M; Ouyang, H (Journal of physics. Conference series, 2009)
Turning is a widely used metal cutting operation. Because of the dynamic interaction between the cutter and the workpiece, vibration is excited during turning operations. If the vibration is severe, there will be degradation of surface quality of the workpiece, excessive wear and breakage of the cutter. Chatter can also take place. This paper presents a dynamic model for aggressive turning operations and considers the influence on vibration of the time-dependent reduction of workpiece diameter. The workpiece is modelled as a beam rotating about its longitudinal axis and the cutter provides a moving load. Simulated numerical examples are presented.